Students’ behaviour in recycling used batteries for pollution prevention: a case study in Malaysia - Farhah Abdillahil Moktamin,; Goh, Choo Ta; Sharina Abdul Halim,; Mazlin Mokhtar,; Mohd Rozaimi Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The best way to manage used batteries without causing adverse effects to the environment is through recycling. The objective of this study to identify relations and factors which encourage the recycling of used batteries by understanding the behaviour and awareness among the students using Theory of Planned Behaviour (TPB). School students in Bangi, Malaysia were selected as case study. A total of 349 respondents from 4 schools located in Bangi (namely SMK Bandar Baru Bangi, SMK Jalan Tiga, SMK Jalan Empat and SMK Dato’ Abu Bakar Baginda) had been chosen using cluster sampling method. The study shows that there are a few significant positive relations, which include infrastructure and behavioural control (r = 0.359); responsibility and behavioural control (r = 0.395); attitude and intention (r = 0.182); willingness to pay and behaviour (r = 0.332). By using regression analysis, the social norm factor is the main factor which encourages recycling of used batteries among respondents based on the TPB theory, and followed by the factors of willingness to pay, attitude and behavioural control.